Адміністративно-правові засади іноземного інвестування в Україні - Федоров, Г. О.; Fedorov, H. O.; ORCID: http://orcid.org/0000-0002-2236-8290 (Вісник Харківського національного університету внутрішніх справ. – 2019. – № 2 (85). – С. 78-86, 2019)
З урахуванням особливостей адміністративно-правових засад розглянуто специфіку іноземного інвестування з позицій комплексного аналізу на сучасному етапі історичного розвитку державного ладу. Враховуючи доктринальні дослідження та власні наукові здобутки, визначено, що сьогодні є надзвичайно актуальним питання реалізації всього комплексу практичних заходів, спрямованих на досягнення якісних змін у питаннях залучення іноземних інвестицій та посилення контролю рівня якості інвестицій в економіку України з позицій адміністративно-правових засад.

The peculiarities of administrative and legal principles of foreign investment from the point of view of complex analysis have been considered, considering the current stage of historical development of the state system. Taking into account doctrinal research and own scientific achievements, it has been determined that nowadays it is extremely urgent to implement the whole set of practical measures aimed at achieving qualitative changes in the issues of attracting foreign investment and strengthening the control over the quality level of investments in the economy of Ukraine from the standpoint of administrative and legal principles. It has been determined and proved that it is expedient to apply the phased approach of administrative and legal regulation of foreign investment – two-step assessment of the quality of foreign investments. In particular, the investor should be evaluated at the first step. This means that the purpose and goals of his investment activity, as well as his investment, business and economic reputation must be assessed. The second stage begins with the evaluation of the investment project, the priority for the economic development of the territorial community, the level of innovation, environmental compatibility, payback period, value of investments, etc. The basis for this approach should be the system for evaluating the quality of the subjects and objects of the investment process. The result of applying this approach should be the definition of the quality of the investment project and definition of the priority for its implementation in accordance with territorial interests. In this regard, it would be appropriate to make a clear distinction between the functions and responsibilities of the institutions that are going to assess the quality of the investments. According to the author, it would be rational to expand the main directions of activity of the Ukrainian Center for Foreign Investment Promotion and to create a special department that would deal with the quality control over the relevant foreign investments coming to the Ukrainian economy. The same structures should be formed at the local level.

С учетом особенностей административно-правовых основ рассмотрена специфика иностранного инвестирования с позиций комплексного анализа на современном этапе исторического развития государственного строя. Учитывая доктринальные исследования и собственные научные достижения, определено, что сегодня чрезвычайно актуальным остается вопрос реализации всего комплекса практических мероприятий, направленных на достижение качественных изменений в вопросах привлечения иностранных инвестиций и усиление контроля уровня качества инвестиций в экономику Украины с позиций административно-правовых основ.
Administrative and Legal Principles of Foreign Investment in Ukraine
Федоров, Г. О. Адміністративно-правові засади іноземного інвестування в Україні / Гліб Омелянович Федоров // Вісник Харківського національного університету внутрішніх справ. – 2019. – № 2 (85). – С. 78-86. - DOI: https://doi.org/10.32631/v.2019.2.07.
Keywords: Адміністративне право та процес. Administrative Law and Procedure. Административное право и процесс; Економічні науки. Економічна безпека. Economics. Economic Security. Экономические науки. Экономическая безопасность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; адміністративно-правові засади; іноземне інвестування; державне регулювання; державне управління; іноземні інвестиції; административно-правовые основы; иностранное инвестирование; государственное регулирование; administrative and legal principles; foreign investment; state regulation; public administration; foreign investment